2017
DOI: 10.1177/0734282917735152
|View full text |Cite
|
Sign up to set email alerts
|

ADHD Assessment in College Students: Psychologists’ Adherence to DSM-5 Criteria and Multi-Method/Multi-Informant Assessment

Abstract: The evidence-based assessment of attention-deficit/hyperactivity disorder (ADHD) depends on adherence to Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5) diagnostic criteria and reliance on multi-method/multi-informant data. Although nearly all psychologists endorse these practices, college students with ADHD may lack documentation supporting their diagnoses. We reviewed the documentation submitted by 214 undergraduates diagnosed with ADHD and receiving academic accommodations for this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 64 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Previous research has shown qualitative differences between the developmental histories and academic functioning of students classified with disabilities at 2-and 4-year colleges (Weis, Sykes, & Unadkat, 2012;Weis, Speridakos, & Ludwig, 2014). Whereas students who receive accommodations at 2-year colleges often have well-documented and longstanding disability histories, most students at 4-year colleges and universities who receive accommodations were not diagnosed with a disability until after beginning college (Sparks & Lovett, 2009;Weis, Till, & Erickson, 2019;. Moreover, the documentation submitted by students at 4-year colleges and universities to support their accommodation requests often lacks evidence that these students experience limitations that merit accommodations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown qualitative differences between the developmental histories and academic functioning of students classified with disabilities at 2-and 4-year colleges (Weis, Sykes, & Unadkat, 2012;Weis, Speridakos, & Ludwig, 2014). Whereas students who receive accommodations at 2-year colleges often have well-documented and longstanding disability histories, most students at 4-year colleges and universities who receive accommodations were not diagnosed with a disability until after beginning college (Sparks & Lovett, 2009;Weis, Till, & Erickson, 2019;. Moreover, the documentation submitted by students at 4-year colleges and universities to support their accommodation requests often lacks evidence that these students experience limitations that merit accommodations.…”
Section: Discussionmentioning
confidence: 99%
“…Although diagnosis of a clinical disorder should be made using accepted diagnostic criteria, a number of recent studies have shown that clinicians rely mainly on student self-report or employ flexible criteria when diagnosing ADHD in young adults (e.g., Harrison, 2017;Joy et al, 2010;Nelson et al, 2019;Weis et al, 2019a). For instance, Joy et al (2010) reviewed ADHD documentation submitted by 50 medical school students in order to obtain accommodations on a licensing exam.…”
Section: Accommodation Decision-making Using Assessor Recommendationsmentioning
confidence: 99%
“…(p. 1786). Similarly, Weis et al (2019a) reviewed 214 assessment reports submitted by university students in support of their ADHD diagnosis. Here, the authors found that 23.4% of clinicians relied on self-report alone, 14% used written documentation, 10% reviewed educational or medical records of the student, and almost none ruled out other possible causes prior to making a diagnosis.…”
Section: Accommodation Decision-making Using Assessor Recommendationsmentioning
confidence: 99%
“…Since many clinicians fail to understand that self-report ADHD questionnaires have a very high false positive rate (e.g., A.G. Harrison et al, 2019), they may not understand that high levels of self-reported symptoms alone are not sufficient to verify the presence of adult ADHD. This lack of awareness may explain why so many clinicians ignore all of the DSM-5 diagnostic guidelines for ADHD and inappropriately rely instead on self-report alone (e.g., Nelson & Lovett, 2019;Weis et al, 2019).…”
Section: Adhd Is Vulnerable To Being Overdiagnosed In Adultsmentioning
confidence: 99%
“…Not all clinicians agree on how to conduct such assessments, and a substantial proportion report a lack of confidence in their ability to reach accurate diagnostic judgments (e.g., Schneider et al, 2019). Furthermore, clinicians who undertake such assessments rarely ensure that all the DSM-5 diagnostic criteria are verified prior to making this diagnosis, at least in young adults (Nelson & Lovett, 2019;Weis et al, 2019) In this introductory article, we briefly review what the empirical literature has shown about selected issues regarding adult ADHD assessment. We then turn to the highlights of each of the remaining articles in the special issue, discussing how they add to our knowledge base.…”
mentioning
confidence: 99%